Réponses

2014-03-20T19:46:32+01:00
A = (1/4 - 1/5) x (7 + 37/9)
A = (1 x 5 / 4 x 5 - 1 x 4 / 5 x 4) x (7 x 9 / 1 x 9 + 37/9)
A = (5/20 - 4/20) x (63/9 + 37/9)
A = 1/20 x 100/9
A = 1 x 100
       20 x 9
A = 100/180
A = 20 x 5 / 20 x 9
A = 5/9

B = 1/9 - 15/9 x 1/6
B = 1/9 - 15 x 1
               9 x 6
B = 1/9 - 15/54
B = 1 x 6 / 9 x 6 - 15/54
B = 6/54 - 15/54
B = -9/54
B = 9 x -1 / 9 x 6
B = -1/6

C = 5/3 - 2/3 : 6/5
C = 5/3 - 2/3 x 5/6
C = 5/3 - 2 x 5
               3 x 6
C = 5/3 - 10/18
C = 5 x 6 / 3 x 6 -10/18
C = 30/18 - 10/18
C = 20/18
C = 2 x 10 / 2 x 9
C = 10/9